Therapeutic approach of cannabidiol on neurodegenerative diseases: evaluation of the effects on the progression of these diseases and their symptoms (Research, Society and Development, 2022)
Several neurodegenerative diseases current therapies, such as for Parkinson’s disease, Alzheimer’s disease and Multiple Sclerosis, need constant improvement, aiming to enhance quality of life, symptomatic improvement, and possibly recovery. Thus, this integrative literature review aims to understand how Cannabidiol (CBD) can be used in the treatment of neurodegenerative diseases, analyzing applicability, therapeutic effects and the method in which this substance is used as this medicinal form. From a search in PubMed, VHL and LILACS databases, articles in English were selected, published between the years 2016 and 2021, which addressed the subject and delved into the effects of CBD on neurodegenerative diseases, specifically: Parkinson's Disease, Multiple Sclerosis, Tuberous Sclerosis, Alzheimer's Disease and Huntington's Disease. After performing the integrative analysis, it was concluded that CBD is a neuroprotective and anti-inflammatory agent, acting to improve motor performance, decrease pain and spasticity. Therefore, it is possible to conclude that, although more studies are needed about its effects and therapeutic mechanisms, cannabidiol is a viable and beneficial substance for use in new therapies for neurodegenerative diseases.